Menstruation Cycle Changes of Implant and Medroksiprogesteron Asetat Injection Acceptor at Puskesmas Karangan Kabupaten Trenggalek - Wenang, Debbie Cahya; Noviana, Ayu Cahyani (Universitas Wijaya Kusuma Surabaya, 2017)
The side effect of Hormonal contraception especially DMPA injection and implant is the changes of menstrual cycle. The changes include amenorrhea, spotting, duration of menstruation, amount of the blood loss etc. 8 of 10 DMPA acceptor has amenorrhea and all of implant acceptor has prolonged period. This research aimed to study the differences changes in menstrual cycle between DMPA Injection and implant acceptor at Puskesmas Karangan, Kecamatan Karangan, Kabupaten Trenggalek. Using cross sectional design and 90 respondents, 45 from DMPA acceptor and 45 from implant acceptor.The result showed that there was differences in menstrual cycle between DMPA injection acceptor with implant acceptor with p = 0,006, CI 95%, contingency coeffisient 0,378. The changes of menstrual cycle lighter for implant acceptor because of differences kind of ingredient.